MASALAH SOSIAL DALAM NASKAH MONOLOG “PRODO IMITATIO” KARYA ARTHUR S. NALAN - Ananda Wiinardo, Regi; Sholeha, Puji; Nazurty (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study aims to describe the forms of social problems contained in Arthur S. Nalan's Prodo Imitatio monologue. This research includes the type of descriptive-qualitative research. The data that the researcher collects is in the form of quotations related to forms of social problems, including poverty, crime, and bureaucracy. With this type of research, the next step is for the researcher to analyze the data that has been collected according to the literature study that the researcher uses and the sociology of literature approach so that the researcher can describe the research data. With qualitative descriptive research, researchers can describe social problems in the monologue text Prodo Imitatio by Arthur S. Nalan